(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Youth unemployment and social fragmentation present existential challenges to Benue State, Nigeria. Dominant narratives often oscillate between the peril of internet fraud (“Yahoo”) and the despair of subsistence agriculture, overshadowing potential pathways for constructive youth engagement. This study investigates the underexplored role of legitimate digital entrepreneurship as a tripartite catalyst for youth empowerment, social cohesion, and future-building. Employing a mixed-methods approach—a survey of 384 digital entrepreneurs across Makurdi, Gboko, and Otukpo, complemented by 25 in-depth interviews and 3 focus group discussions—the research is framed by Sen’s Capability Approach and Social Capital Theory. Preliminary findings indicate that digital entrepreneurship significantly enhances participants’ economic agency, skills, and self-worth (empowerment). Furthermore, collaborative digital hubs and online communities are fostering new, non-ascriptive identities that bridge ethnic divides, particularly between the Tiv, Idoma, and Igede youth (social cohesion). Despite severe infrastructural and financial constraints, these ventures are building resilient economic futures and altering intergenerational aspirations. The study concludes that targeted policy interventions in digital infrastructure, youth-focused e-enterprise funds, and the incubation of tech hubs in tertiary institutions can systematically harness this potential. This research contributes to the literature on youth, digital economies, and peacebuilding in conflict-prone regions of Sub-Saharan Africa.